MEASURING THE LEVEL OF RURAL DEVELOPMENT OF UPPER DANUBE REGION - Његован, Зоран; Пејановић, Радован; Марковић, Катарина (Economics of Agriculture, 2011)
The authors are trying to analyse the problems of rural development and defne the rural municipalities within the Upper Danube region. They are using the rural indicators that are suggested by OECD and EU according to the subjects and more of that, to construct the composite indicator as a unique measure for the level of rural development and the base for the rural policy conceptualisation in Upper Danube region.